THE SOCIAL FUNCTION OF GREEN OPEN SPACE : A CASE STUDY TEGALLEGA PARK BANDUNG - Sabrina Rafifah. A. D. P; Etty Indrawati; Reza Fauzi (Universitas Trisakti, 2024)
The use of as a public green open space is considered less effective, as various activities or facilities are not in accordance with its function. This causes a decline in the physical and biophysical conditions of Tegalega Park's social function. Indicators of Tegalega Park as a social function can be seen from the location, vegetation cover, area, multifunctional park, and type of vegetation. Meanwhile, indicators of social function are the presence of city characteristics and landmarks as a means of recreation, children's play, education and research, and sports facilities. This research aims to evaluate public green open space activity facilities as a social function in Tegalega Park. The research method was carried out using field observations, interviews, and literature studies related to regulations and theories. Data analysis was carried out by triangulation by comparing several sources of data that had been obtained against provisions based on applicable laws and standards. The results of the research show that the vegetation cover in Tegalega Park as a green open space is still 48%. There is a need to divide the space to group various activities so that they are more organized and directed. Lack of supporting facilities such as gazebos, rubbish bins, and signboards; historical information on monuments; and information on tree identities. The implications of these findings can help in more effective planning and management of the development of the social function of Tegalega Park as a public green open space.